(untitled) (Comparatismi, 2025)
Homesickness has been a foundational theme of Western literature, long before 17th‑century medicine coined the term nostalgia. Initially described as a clinical pathology, the concept has since evolved into a complex psychological experience in which the spatial dimension (home) intersects with the temporal dimension (origin). Recent neurocognitive studies highlight its beneficial and adaptive potential, and this reevaluation has sparked an explosion of interest in looking backward across social, economic, and cultural spheres. In this context, algorithms and media play a boosting role, both as vectors of nostalgic content and as nostalgic objects themselves. Moreover, beyond its thematic preoccupation, literature offers a distinctive form of media nostalgia in which the book – particularly in postdigital storytelling – emerges as the privileged medium for a literary nostalgia that copes with the trauma of a digitized present and the obsolescence of the printed medium.